Too Early to Cut Transportation Benefits From Medicaid Enrollees - Krisda H Chaiyachati; Kevin Moore; Michael Adelberg (SAGE Publishing, 2018)
Some state governments are considering cuts to the non-emergency medical transportation (NEMT) benefit for Medicaid enrollees, and some Federal officials have proposed making this easier. Yet, there is clear demand. In 2015 alone, low-income patients used 59 million rides for medical appointments. NEMT's future is under threat because evidence that NEMT improves health care access and downstream outcomes is incomplete. Second, it remains largely unknown whether scarce public resources for transportation are being driven to those who benefit from its availability. This knowledge gap is answerable but unknown because of variations in how states administer NEMT. As a result, tracking who uses the services is inconsistent, and states are unable to link NEMT data with health care outcomes. Instead of cutting NEMT benefits, we believe an alternative path involves improved tracking and evaluations of the benefit first. Better informed policy decisions are needed. Otherwise, if policymakers implement blanket reductions in NEMT spending, they run the risk of causing more harm than good.